If it's not what You are looking for type in the equation solver your own equation and let us solve it.
N in (-oo:+oo)
(3/14)*N = 3/16 // - 3/16
(3/14)*N-(3/16) = 0
(3/14)*N-3/16 = 0
3/14*N-3/16 = 0 // + 3/16
3/14*N = 3/16 // : 3/14
N = 3/16/3/14
N = 7/8
N = 7/8
| (4t+5)(3t+10)=0 | | -8+3x=-4x+55 | | -2(x+1)+x=7-4x | | x-[5+3x-[5x-(6+x)]]=-3 | | 2X=4/15 | | 6x+1=3x+4 | | y+15=-30 | | x-2x+12-3x=-5(x-2)+2 | | 8+3n=-2a+24 | | 2x-6-8=0 | | 4-2x=8+.5x | | -4x-3=6x-123 | | -0x+10-3x=-5(x-2)+2 | | x+22+3x=-19-3x-22 | | -2x+9-3x=-5(x-2)+2 | | -2x+12-3x=-5(x-2)+0 | | -2x+12-3x=5(x-2)+2 | | 4+3x=7x-24 | | 3(s+2)-(2s-3)=5 | | 3x^2-3x=21 | | 3x+8y+2=0 | | 4x=(-8) | | 5/8*8/5 | | -2x+12-3x=-5(x-2)+3 | | 2x+12-2x=-5(x-2)+2 | | 4x+3y-5=0 | | 8+3x=6x+26 | | -4x+12-2x=-5(x-2)+2 | | x+6-x-4=10-x | | 6x+y=8x-2y | | 4x+2(x+1)=26 | | 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 |